Camellia sinensis Ameliorates the Efficacy of Last Line Antibiotics Against Carbapenem Resistant Escherichia coli. (1st December 2015) - Thakur, Pallavi; Chawla, Raman; Chakotiya, Ankita Singh; Tanwar, Ankit; Goel, Rajeev; Narula, Alka; Arora, Rajesh; Sharma, Rakesh Kumar
Abstract : Aquo‐ethanolic extract of Camellia sinensis (PTRC‐31911‐A), standardized using Fourier transform infrared analysis, was found to have seven common functional groups in comparison with pre‐identified marker compound 'quercetin'. Phyto‐chemical quantitation analysis revealed the presence of 10.65 µg/mg of flavonoids. The bioactivity fingerprint profile of PTRC‐31911‐A includes IC50 (Hydroxyl radical site specific scavenging)  = 11.36 ± 0.5 µg/mL, IC80 (Hydroxyl radical non‐site specific scavenging)  = 26.44 ± 0.5 µg/mL and IC50 (Superoxide ion scavenging)  = 10.141 ± 0.5 µg/mL. The drug combination analysis of PTRC‐31911‐A with five third‐line antibiotics was carried out against carbapenem‐resistant Escherichia coli . The analysis of combination of PTRC‐31911‐A (6.25–1000 µg/mL) and antibiotics (6.25–1000 µg/mL) revealed synergistic behaviour (fractional inhibitory concentration indices < 1) with tigecycline, ertapenem, meropenem, colistin and augmentin. The lead combination of PTRC‐31911‐A + ertapenem or meropenem showed maximum augmentative potential at 50 and 100 µg/mL, respectively, with nearly five‐fold decrease in minimum inhibitory concentrations as compared with respective antibiotics alone. The synergistic effects implied that the antibacterial combinations of PTRC‐31911‐A and ertapenem, meropenem, colistin, tigecycline or augmentin would be more effective than a single monotherapy with either of the antibacterial agent. Copyright © 2015 John Wiley & Sons, Ltd.